A Coupled 1D-2D Hydrodynamic Model for Urban Flood Inundation. (23rd May 2017) - Fan, Yuyan; Ao, Tianqi; Yu, Haijun; Huang, Guoru; Li, Xiaodong
Abstract : Hydrodynamic models were commonly used for flood risk management in urban area. This paper presents initial efforts in developing an urban flood inundation model by coupling a one-dimensional (1D) model with a two-dimensional (2D) model to overcome the drawbacks of each individual modelling approach, and an additional module is used to simulate the rainfall-runoff process in study areas. For the 1D model, the finite difference method is used to discretize the Saint-Venant equations. An implicit dual time-stepping method (DTS) is then applied to a 2D finite volume model for an inundation simulation to improve computational efficiency. A total of four test cases are applied to validate the proposed model; its performance is demonstrated by a comparison with an explicit scheme and previously published results (an extensive physical experiment benchmark case, a vertical linking example, and two real drainage cases with actual topography). Results demonstrate that the proposed model is accurate and efficient in simulating urban floods for practical applications.